Advances in SLA Monitoring, Root Cause Analysis, and Vendor Compliance in Next-Generation Networks - Nasiru Hayatu; Abraham Ayodeji Abayomi; Abel Chukwuemeke Uzoka (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
As next-generation networks (NGNs) such as 5G, edge computing, and software-defined infrastructures become the new standard in global telecommunications, the complexity of maintaining service level agreements (SLAs), diagnosing failures, and ensuring vendor compliance has intensified. This systematic review explores recent advances in SLA monitoring, root cause analysis (RCA), and vendor compliance frameworks in NGNs. The study synthesizes insights from 88 peer-reviewed articles, technical standards, and industry whitepapers published between 2015 and 2024, using a PRISMA-based methodology to evaluate technological innovations and emerging best practices. Findings reveal a shift from traditional rule-based SLA monitoring to dynamic, AI-driven models that enable real-time detection and prediction of SLA breaches. These models incorporate machine learning algorithms, anomaly detection, and adaptive thresholds, which significantly enhance the accuracy and responsiveness of performance monitoring systems. Furthermore, advancements in RCA leverage graph-based approaches, causality inference models, and intent-based networking to isolate fault origins with high precision in complex, multi-layered network environments. Vendor compliance in NGNs is increasingly managed through automated compliance engines integrated with digital contracts and blockchain-based auditing mechanisms. These tools offer transparent, tamper-resistant tracking of vendor activities against agreed SLA metrics. Case studies highlight how telecom operators now embed smart contracts and compliance triggers into orchestration layers to enforce accountability and streamline remediation processes. However, gaps persist in cross-domain SLA standardization, data interoperability, and vendor-agnostic frameworks that support unified monitoring across heterogeneous infrastructures. Additionally, regulatory fragmentation across markets impedes seamless SLA enforcement, especially in multi-vendor or cross-border deployments. This review proposes a consolidated framework for SLA assurance that integrates AI-driven monitoring, context-aware RCA, and compliance automation. The framework offers a pathway for telecom operators, equipment vendors, and regulatory bodies to collaborate in delivering resilient, transparent, and customer-centric services in the NGN era.